KAJIAN ECONOMIC ANALYSIS OF LAW : UNTUK SEBUAH ARBITRASE KOMERSIAL YANG BERNILAI EKONOMIS - puspita, lona (Fakultas Hukum Universitas Tamansiswa Padang, 2024)
The problem that often occurs in arbitration settlements is disharmony between one statutory regulation and another statutory regulation resulting in inefficiency, namely between Article 3 UUAAPS, Article 11 UUAAPS and Article 10 paragraph (1) of Law Number 48 of 2009 concerning Power. Justice. So the problem in this writing is how to study Economic Analysis of Law in realizing a commercial arbitrage that has economic value. The results of the discussion stated that the existence of international commercial institutions in resolving disputes in Indonesia cannot be said to be effective because there are still inefficiencies among existing regulations. Therefore, efficiency theory is needed in making legal regulations so that these regulations can provide legal certainty to the public.